Arterial thrombus formation - Hagedorn, I.; Vögtle, T.; Nieswandt, B. (Hämostaseologie, 2010)
Platelet and coagulation factor-dependent thrombus formation is critical to limit post-traumatic blood loss at sites of vascular injury. However, under pathological conditions like rupture of an atherosclerotic plaque, it may also lead to vessel occlusion causing myocardial infarction or stroke. Therefore, antithrombotic treatment is the prime therapeutic option in the prophylaxis and treatment of ischaemic cardio- and cerebrovascular diseases. The use of existing antithrombotic agents is, however, limited by their inherent effect on primary haemostasis. In recent years, major advances have been made in understanding the mechanisms of thrombus formation in haemostasis and thrombosis and some studies raised the interesting possibility that occlusive thrombus formation and haemo stasis may involve partially different mechanisms. This review briefly summarizes these developments and highlights newly identified mechanisms involved in platelet adhesion and activation, intracellular calcium signaling, integrin activation and initiation of coagulation. The suitability of these pathways as novel targets for antithrombotic therapy is discussed.
Keywords: Platelets; thrombus formation; factor XII; integrin activation